MODEL PENGEMBANGAN MINAT DAN BAKAT MAHASISWA - Dyah Fitriani; Hendro Setyono (Yayasan Hurriah, Banda Aceh, 2022)
Engish: Human resources are important aspect in an organization. Student needs to be managed and developed in a manner that benefits for them and the progress of departement.Online learning be implemented in full during covid-19 pandemic. The development of their interests and talent to be challenges for departement.The purpose of this research is to formulate a model of student interests and talents in management deprtment. In addition, the purpose of this research is to find a map of student’s interests and talents on the academic and non academic so as to improve their performance at national and international levels. The questionnaire used as a method of collecting the data and focus group discussion used as a method of formulate model of development student’s interests and talents .The result of this research are : 1) students study of management departement has an interest joining Program Kreativitas Mahasiswa (PKM) competitions and business plan competition but of less intention to join the debate. 2) Students has an interest in some sports (badminton, football and futsal) and had achievements in arts (dance, music, calligraphy and movie maker). 3) Development strategy of student’s interests and talents through several phases : the mapping of potentials students and scheduling of competition in a year, collaboration with the student organisations to get talented students, the commissioning of counterpart lecturers, the making of community, the establishment of a community, the delivery of the competition and evaluation of the program. Bahasa: Sumber daya manusia menjadi aspek penting dalam suatu organisasi. Mahasiswa sebagai bagian penting dari program studi perlu dikelola dan dikembangkan dengan baik sehingga dapat memberi manfaat untuk mahasiswa dan kemajuan program studi. Pembelajaran dilaksanakan secara full online selama pandemi covid-19. Pengembangan minat dan bakat mahasiswa menjadi tantangan tersendiri bagi program studi. Tujuan penelitian ini adalah merumuskan suatu model pengembangan minat dan bakat mahasiswa Program Studi Manajemen. Selain itu, tujuan penelitian ini adalah untuk mengetahui peta minat dan bakat mahasiswa Program Studi Manajemen pada bidang akademik dan non akademik sehingga dapat meningkatkan prestasi di tingkat nasional dan internasional.Kuesioner digunakan sebagai metode pengambilan data dan focus group discussion digunakan sebagai metode untuk merumuskan model pengembangan minat dan bakat. Hasil penelitian ini adalah: (1) mahasiswa Program Studi Manajemen memiliki minat mengikuti lomba Program Kreativitas Mahasiswa (PKM) dan Business Plan Competition namun kurang berminat mengikuti lomba debat. (2) Mahasiswa Program Studi Manajemen memiliki minat pada beberapa cabang olahraga diantaranya badminton, sepakbola dan futsal serta memiliki prestasi di bidang seni berupa seni tari, seni suara, seni musik, seni kaligrafi dan film. (3) Strategi pengembangan minat dan bakat melalui beberapa tahapan yaitu: pemetaan potensi mahasiswa dan inventarisasi lomba-lomba dalam satu tahun, bekerjasama dengan organisasi mahasiswa untuk penjaringan mahasiswa, penunjukan PIC dosen pendamping, pembentukan komunitas, pembinaan komunitas, pengiriman lomba dan evaluasi program